â€œBERLAYAR MENUJU PULAU DEWATAâ€ MIGRASI ORANG-ORANG BUGIS-MAKASSAR KE BALI UTARA â€œSAILING TO THE ISLAND OF GODSâ€ MIGRATION OF BUGINESE-MAKASSARESE TO NORTH BALI - Johny A. Khusyairi; Abd. Latif; Samidi Samidi (Jurnal Masyarakat dan Budaya, 2016)
Abstract This article aims to discuss the migration process of the Buginese-Makassarese to north Bali. Based on oral history, they had lived in north Bali since the 17th century. They later settled down in the kampongs of Buginese in Buleleng, Penyabangan, Celukan Bawang, and Sumberkima. The migration process was driven by political and economic problems. The Makassarese and their allies was lost during their struggle against the Dutch-East India Company (VOC) in 1667/1669. The migration flow of Makassarese was increasing due to the rebel of Kahar Muzakar DI/TII in South Sulawesi. Economically, they have sails to catch sea cucumbers and turtles then sell them to Singapore. The Buginese-Makassare always preserve their Bugineseness identity while they are interacting with the Balinese. Nevertheless, some aspects of their identity are gradually disappearing, such as ethnic language and house architecture. Although they have different religion and belief, they can adapt to the Balinese customs and culture. Using Balinese language and marriage with Balinese are the media to maintain their relationships with the locals. Keywords: migration, Buginese-Makassarese, North Bali, adaptation Abstrak Artikel ini bertujuan untuk mendiskusikan proses migrasi orang-orang Bugis-Makassar ke Bali Utara. Berdasarkan tradisi dan sejarah lisan, mereka sudah berada di Bali Utara sejak abad ke-17. Mereka bermukim di Kampung Bugis Buleleng, Penyabangan, Celukan Bawang, dan Sumberkima. Proses migrasi didorong oleh persoalan politik dan ekonomi. Persoalan politik berkaitan dengan kekalahan Makassar dan sekutunya melawan VOC pada tahun 1667/1669. Gelombang migrasi besar-besaran terjadi saat Sulawesi Selatan dilanda kekacauan akibat pemberontakan DI/TII Kahar Muzakkar. Persoalan ekonomi juga menjadi alasan penting dalam proses migrasi tersebut. Mereka berlayar ke berbagai kawasan untuk mencari teripang dan penyu untuk dijual ke Singapura. Dalam perjumpaan dengan orang-orang Bali yang memiliki adat- istiadat, orang-orang Bugis-Makassar tetap mampu menjaga identitas ke-Bugis-annya. Akan tetapi, terdapat beberapa aspek yang mulai hilang seperti bahasa dan rumah. Walaupun memiliki perbedaan keyakinan, orang-orang Bugis-Makassar mampu beradaptasi dengan orang-orang Bali. Bahasa dan perkawinan dengan orang Bali menjadi media untuk menjaga hubungan mereka dengan penduduk lokal. Kata kunci: migrasi, Bugis-Makassar, Bali Utara, adaptasi